Modeling and optimization of multiple tuned mass dampers for a barge-type floating offshore wind turbine - Wang, Bin; Han, Dongdong; Wang, Wenhua; Li, Xin; Shen, Kanmin; Li, Ying (Frontiers in Marine Science, 2022)
Significant structural responses pose potential hazards to the safe operation of floating offshore wind turbines (FOWTs). To effectively mitigate the motion of FOWTs using conventional passive vibration control methods such as tuned mass damper (TMD) and multiple tuned mass damper (MTMD), an optimization method for TMD and MTMD in a barge-type FOWT is proposed in this study. A simplified dynamic model of a barge FOWT with MTMD, which includes the tower first bending and floating platform degrees of freedom (DOFs), in addition to the simplified DOF of the MTMD, is derived. The corresponding fully coupled numerical model is established using the updated simulation tool FAST-SC. Subsequently, the unknown parameters and accuracy of the simplified dynamic model are validated via comparison with the results of the coupled numerical model. Moreover, an optimization method is proposed based on the simplified dynamic model considering the prominent coupling effects of FOWT and computational expense, and the GA algorithm is used for TMD and MTMD optimization. Furthermore, the effectiveness of the optimized TMDs and MTMD is evaluated based on the reduction in the coupled responses of the barge FOWT under the selected environmental conditions. Compared with the optimized TMD in the nacelle, the optimized TMD in the platform and MTMD are proven to be more feasible for vibration mitigation under complex environmental loads. Moreover, an improved steady output is obtained using the optimized vibration control methods, in addition to the excellent mitigation effects on structural responses.